The perceptions of STEM tutors on the role of tutorials in distance learning. (2nd January 2019) - Campbell, Anne; Gallen, Anne-Marie; Jones, Mark H.; Walshe, Ann
ABSTRACT: As part of a wider study into perceptions that different university stakeholders have of tutorials, we investigated the UK Open University model for tuition through a process of semi-structured interviews with a self-selecting set of STEM tutors. The aim of the study was to elucidate perceptions that tutors have of the role and purpose of tutorials, and their perceptions of student expectations of group tuition. Thematic analysis of interview transcripts using a grounded theory approach identified several key themes. These include perceptions of the tutor role in group tuition: facilitating academic learning and skills; and supporting the building of confidence, motivation, social interaction and collaborative group-work skills. Difficulties were identified in encouraging student interaction in online synchronous tuition. In addition, mismatches became apparent between tutors' perceptions of student expectations of tuition and their own preferred approaches, with suggestions that students expect a didactic rather than interactive experience.